2015
DOI: 10.1016/j.dcn.2015.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent drinking and brain morphometry: A co-twin control analysis

Abstract: Developmental changes in structure and functioning are thought to make the adolescent brain particularly sensitive to the negative effects of alcohol. Although alcohol use disorders are relatively rare in adolescence, the initiation of alcohol use, including problematic use, becomes increasingly prevalent during this period. The present study examined associations between normative drinking (alcohol initiation, binge drinking, intoxication) and brain morphometry in a sample of 96 adolescent monozygotic twins. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 42 publications
7
39
0
Order By: Relevance
“…Human brain imaging studies have identified neural functioning correlates of adolescent heavy drinking. Studies using co-twin designs have found that amygdala deficits (Wilson et al , 2015), smaller orbitofrontal cortex volumes and diminished quality of decision making (Malone et al , 2014) are associated with adolescent alcohol use. Brain imaging studies examining singletons have found that young people with alcohol use disorders have smaller hippocampal volumes (De Bellis et al , 2000; Nagel et al , 2005), prefrontal abnormalities at both the structural (De Bellis et al , 2005) and functional levels (Tapert et al , 2004), and damage to the frontal lobe (Crews et al , 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Human brain imaging studies have identified neural functioning correlates of adolescent heavy drinking. Studies using co-twin designs have found that amygdala deficits (Wilson et al , 2015), smaller orbitofrontal cortex volumes and diminished quality of decision making (Malone et al , 2014) are associated with adolescent alcohol use. Brain imaging studies examining singletons have found that young people with alcohol use disorders have smaller hippocampal volumes (De Bellis et al , 2000; Nagel et al , 2005), prefrontal abnormalities at both the structural (De Bellis et al , 2005) and functional levels (Tapert et al , 2004), and damage to the frontal lobe (Crews et al , 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Prior research offers strong support for the construct and psychometric validity of this composite index, including high internal consistency and expected parent-offspring correlations when assessed throughout adolescence (McGue et al, 2014). In addition, higher index scores have been associated with reduced prefrontal grey matter volume and neurocognitive performance in adolescents (Malone et al, 2014; Wilson et al, 2015), and diminished response inhibition-related theta-band MFC power and MFC-dPFC connectivity in young adults (Harper et al, 2016). …”
Section: Methodsmentioning
confidence: 99%
“…Specifically, heavy drinking adolescents exhibit reduced grey and white matter prefrontal cortex volume (Bellis et al, 2005; Medina et al, 2008; Malone et al, 2014; Wilson et al, 2015) and suboptimal performance on laboratory tasks of executive functioning (Nigg et al, 2006; Squeglia et al, 2009; Malone et al, 2014) compared to adolescents with limited or no history of alcohol exposure. Because most of this research was conducted using cross-sectional observational research designs, less is known about any long-term neurocognitive effects of AAU, nor is it known to what degree neurocognitive dysfunction is a manifestation of the genetic propensity to abuse alcohol versus a consequence of misuse.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because adolescence is a critical period of brain development, teenage binge alcohol consumption has the potential to produce long-lasting effects on health and behavior beyond the immediate effects of being acutely intoxicated. Teenagers who drink alcohol have region-specific cortical thinning and white matter disorganization (Luciana et al, 2013; Wilson et al, 2015). In addition to these anatomical changes, adolescent binge drinking increases the risk for developing alcohol dependence and other mental health disorders during adulthood (McCambridge et al, 2011; Rose et al, 2014; Viner and Taylor, 2007).…”
Section: Introductionmentioning
confidence: 99%